The electronic spectra of vacancies in ZnS, ZnSe and ZnTe - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The electronic spectra of vacancies and their various charged states in cubic ZnS, ZnSe and ZnTe crystals are calculated by the Green's function approach within the localized orbital method. The trends in the levels of charged vacancies are determined by taking into consideration the overall charge neutrality condition. The pressure effects and the relaxation along (I 11) direction on the Zn and Se vacancy levels are also examined. The calculated results can be easily transferred to the calculation of vacancy induced optical properties. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: charged vacancy levels; vacancies; Green's function; localized orbital method (LOM); SEMICONDUCTORS; DEFECTS